PENILAIAN SAHAM PT PEMBANGUNAN PERUMAHAN PROPERTI DALAM RANGKA INITIAL PUBLIC OFFERING - Rifki Khoirudin (Jurnal Keuangan dan Perbankan, 2017)
This research aimed to estimate fair value per share of PT Pembangunan Perumahan Property Tbk. as a comparison value to the offered price, set at the time of Initial Public Offering (IPO). This research also aimed to determine whether the price offered at the time of IPO was undervalued or overvalued. Information used in this research was in the form of secondary data of PT Pembangunan Perumahan Property, the financial report of comparable companies, and stock prices of comparable companies. The analyzing tools used to determine the fair value per share were discounted cash flow method and the relative valuation method. The discounted cash flow method was performed through the projection of the financial statements i.e. the balance sheet and income statement, the projection of Free Cash Flow to Equity (FCFE), determination of the discount rate, determination of terminal value, and determining the estimated value of the equity. The relative valuation method was established by searching, choosing and determining the appropriate multiple of comparable companies in similar business. Multiples used were: Price Earnings Ratio (PER), Price to Book Value (PBV), and Price to Sales Ratio (P/S).